Effect of ZnO particle sizes on thermal aging behavior of natural rubber vulcanizates. (February 2018) - Lee, Yong Hwan; Cho, Misuk; Nam, Jae-Do; Lee, Youngkwan
Abstract: The effects of ZnO particle size on crosslinking and thermal aging behavior of natural rubber (NR) were investigated. NR vulcanizates filled with nano ZnO allowed higher crosslink density, lower polysulfide crosslink, and stronger mechanical properties than those filled with micro ZnO. After thermal aging, NR filled with nano ZnO exhibited much more stable chemical and mechanical properties. The high crosslink density as well as the formation of more stable mono- and di-sulfidic crosslinks was attributed to the good dispersion and high surface area of the nano ZnO. Highlights: The effects of ZnO particle size on crosslinking and thermal aging of natural rubber (NR) were investigated. High crosslink density as well as the formation of more stable crosslinks was attributed to high surface area of nano ZnO. NR vulcanizates with nano ZnO exhibited high retention of mechanical properties after thermal aging.